Factors Affecting Sexual Health after Puerperium among Women in Karachi: Factors Affecting Sexual Health After Puerperium - Mustafa, Rozina; Munaver, Sagheera Anjum; Tufail, Amber; Malik, Zuyyan Irfan; Malik, Hurais (Pakistan Journal of Health Sciences, 2025)
The puerperium phase represents a critical juncture in a woman’s reproductive journey, marked by significant physical, emotional, and relational adjustments. Various factors beyond the mere resumption of sexual activity influence sexual well-being during this period. However, discussions surrounding postpartum sexual health remain limited, particularly in low- and middle-income countries like Pakistan. Objectives: To explore postpartum sexual health in Pakistani women, identifying cultural, physical, and emotional factors influencing well-being. Methods: A cross-sectional study was conducted at Fazaia Ruth Pfau Medical College (FRPMC) Hospitals in Karachi from August 2022 to July 2023. Within the first three months’ post-puerperium, 263 women aged 18 to 45 participated. A comprehensive questionnaire, developed and validated through rigorous processes, assessed socio-demographic, obstetric, and sexual health factors. Statistical analyses, including chi-square tests and Kendall’s tau correlation analyses, were employed. Results: Participants exhibited diverse socio-demographic and obstetric profiles, with a notable prevalence of resumption of sexual activity (65.1%) and concerns such as dyspareunia (66.5%) and decreased libido (53.2%). Significant associations were found between various socio-demographic and obstetric factors and postpartum sexual health outcomes. Longer marriage duration was associated with higher libido levels, while the mode of delivery and the last baby’s birth weight influenced coital frequency. Age, marriage duration, and parity affected postpartum libido, vaginal dryness, and dyspareunia. Conclusions: It was concluded that this study provides valuable insights into the complexity of postpartum sexual experiences among women in Karachi, Pakistan. The findings underscore the need for comprehensive, culturally sensitive interventions to support women’s sexual well-being during this critical period.